2017
DOI: 10.1016/j.jcp.2017.05.052
|View full text |Cite
|
Sign up to set email alerts
|

A fast Chebyshev method for simulating flexible-wing propulsion

Abstract: We develop a highly efficient numerical method to simulate small-amplitude flapping propulsion by a flexible wing in a nearly inviscid fluid. We allow the wing's elastic modulus and mass density to vary arbitrarily, with an eye towards optimizing these distributions for propulsive performance. The method to determine the wing kinematics is based on Chebyshev collocation of the 1D beam equation as coupled to the surrounding 2D fluid flow. Through small-amplitude analysis of the Euler equations (with trailing-ed… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
49
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(53 citation statements)
references
References 89 publications
4
49
0
Order By: Relevance
“…Various groups have conducted numerical simulations of the Navier-Stokes equations coupled to an immersed body's dynamics, and have thus studied flapping wings [51][52][53][54][55] and deformable bodies with more realistic fish-like kinematics [56][57][58][59][60][61][62][63]. Hemelrijk et al [64] and Daghooghi et al [65] modeled a fish school by numeri-cally simulating a swimmer with doubly-periodic boundary conditions in 2D and 3D, respectively, and found that swimmers move faster in schools than in isolation.…”
Section: Introductionmentioning
confidence: 99%
“…Various groups have conducted numerical simulations of the Navier-Stokes equations coupled to an immersed body's dynamics, and have thus studied flapping wings [51][52][53][54][55] and deformable bodies with more realistic fish-like kinematics [56][57][58][59][60][61][62][63]. Hemelrijk et al [64] and Daghooghi et al [65] modeled a fish school by numeri-cally simulating a swimmer with doubly-periodic boundary conditions in 2D and 3D, respectively, and found that swimmers move faster in schools than in isolation.…”
Section: Introductionmentioning
confidence: 99%
“…Here, the setup and assumptions are the same as in Moore [2017]. Consider a two-dimensional, inextensible elastic plate of length L and thickness d. The plate is thin (d L), and is transversely deflected a small amount Y from its neutral position, with its slope Y x 1.…”
Section: Problem Descriptionmentioning
confidence: 99%
“…where C T S is the leading edge suction force (formula given in Moore [2017]), and the power input is…”
Section: Problem Descriptionmentioning
confidence: 99%
“…Here, the setup and assumptions are the same as in Moore (2017). Consider a twodimensional, inextensible elastic plate of length L and thickness d. The plate is thin (d L), and is transversely deflected a small amount Y from its neutral position, with its slope Y x 1.…”
Section: Problem Descriptionmentioning
confidence: 99%
“…The leading edge suction force used in Moore (2017) is the limit of the suction force on a leading edge of small but finite radius of curvature, in the limit that the radius tends to zero. The leading edge suction force is a reasonable model of the actual flow when it is attached (Saffman 1992), so we have chosen to include it.…”
Section: Problem Descriptionmentioning
confidence: 99%